Neuroprotection and Stroke Rehabilitation: Modulation and Enhancement of Recovery - José Rafael Romero; Viken L. Babikian; Douglas I. Katz; Seth P. Finklestein (Behavioural Neurology)
Recent advances in research are modifying our view of recovery after nervous system damage. New findings are changing previously held concepts and providing promising avenues for treatment of patients after stroke. This review discusses mechanisms of neuronal injury after brain ischemia and the attempts to study neuroprotection options based on such mechanisms. It also considers measures available at present to improve outcome after stroke and presents new areas of research, particularly stimulation techniques, neurogenesis and trophic factors to enhance recovery. In order to improve outcomes, medications that may be detrimental to recovery should be avoided, while symptomatic therapy of problems such as depression, pain syndromes and spasticity may contribute to better results. Continued surveillance and early treatment of complications associated with acute stroke, along with supportive care remain the mainstay of treatment for stroke patients in the recovery phase. Present research on limiting brain damage and improving recovery and plasticity enhance the prospects for better clinical treatments to improve recovery after stroke.